Trends in Library Science Research Topics During the Period 2016-2019 - Muh. Quraisy Mathar; Ayu Trysnawati (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2021)
Since its establishment in 1999, the Library Science Department of UIN Alauddin Makassar have been producing hundreds of researches in the field written by its alumni. This bibliometric study described the trend of research topics written by the undergraduate library science students in the department during the period 2016-109. It also described the various types of documents cited as references in the researches. 336 undergraduate theses were obtained from the faculty library database. It is found that there were 19 categories of research topics that had written during the period. There were 5 trends in research topics that are most frequently studied, namely Library Collections 22,09 %, Librarians 12,14 %, Library Services and Librarian 8,25 %, and Library Technology 8,01 %. This research can have implications for the design of new formulas regarding the direction and objectives of research in the field of library science in the future.